Selenium Reduces Cadmium-Induced Cardiotoxicity by Modulating Oxidative Stress and the ROS/PARP-1/TRPM2 Signalling Pathway in Rats - Yazğan, Yener; Keleş, Ömer Faruk; Bayir, Mehmet Hafit; Çiçek, Hacı Ahmet; Ahlatcı, Adem; Yıldızhan, Kenan (MDPI AG, 2025)
Cadmium (CAD) is a prevalent environmental contaminant that poses serious cardiotoxic risks. The heart, kidney, liver, and brain are just a few of the essential organs that can sustain serious harm from CAD, a very poisonous heavy metal. The cardiotoxic mechanism of CAD is linked to oxidative damage and inflammation. A trace element with anti-inflammatory, anti-apoptotic, and antioxidant qualities, selenium (SEL) can be taken as a dietary supplement. The biotoxicity of heavy metal CAD is significantly inhibited by SEL, a mineral that is vital to human and animal nutrition. Through ROS-induced PARP-1/ADPR/TRPM2 pathways, this study seeks to assess the preventive benefits of selenium against cardiovascular damage caused by CAD. The SEL showed encouraging results in reducing inflammatory and oxidative reactions. Rats were given 0.5 mg/kg SEL and 3 mg/kg 2-Aminoethyl diphenylborinate (2-APB) intraperitoneally for five days, in addition to 25 mg/kg CAD given via gavage. Histopathological examination findings revealed that the morphologic changes in the hearts of the CAD group rats were characterised by marked necrosis and the degeneration of myocytes and congestion of vessels. Compared to the rats in the CAD group, the hearts of the SEL, 2-APB and SEL+2-APB groups showed fewer morphological alterations. Moreover, in rats given CAD, there was an increase in cardiac malondialdehyde (MDA), total oxidant (TOS), reactive oxygen species (ROS), caspase (Casp-3-9), and TNF-α, whereas glutathione (GSH), glutathione peroxidase (GSH-Px), superoxide dismutase (SOD) and total antioxidant (TAS) decreased. SEL improved antioxidants, avoided tissue damage, and reduced cardiac MDA, TOS, and ROS. In rats given CAD, SEL decreased cardiac PARP-1, TRPM2, TNF-α, and caspase. In summary, by reducing oxidative stress and cardiac damage and modifying the ROS/PARP-1/TRPM2 pathway, SEL protected against CAD cardiotoxicity.
Keywords: Article